Features of ignition and combustion of a twocomponent gas suspension of coal particles - Orlovskaya, S.G.; Zuj, O.N.; Chernyak, V.Ya. (Вопросы атомной науки и техники, 2018)
Physical and mathematical modeling of high-temperature heat and mass transfer and combustion kinetics of a two-fraction gas suspension of carbon particles at different gas temperatures is carried out. It was assumed that two parallel chemical reactions occur on the surface of the carbon particles: C + O₂ = CO₂ (I), 2C + O₂ = 2CO (II). Molecular-conjugate heat exchange of particles with gas was taken into account, as well as heat exchange by radiation with the walls of the reaction apparatus. As a result of the numerical experiment, the characteristics of ignition and combustion of gas-suspension particles in air at various temperatures of the surrounding gas are determined. For calculations, a two-fraction gas suspension was chosen with equal mass fractions and particle diameters, which differ by a factor of 2: db₁ = 60 μm, db₂ = 120 μm. The range of the initial gas temperatures studied is 1100…1500 K. As a result of the calculations carried out, it was established that as the gas temperature decreases, the coarse fraction can ignite earlier than the fine fraction. At high gas temperatures, on the contrary: the induction period of fine particles is much larger than the period of induction of coarse particles. Critical parameters of ignition of two-fraction gases are found. The main characteristics of combustion are the time and temperature of combustion of the particles. It is proved that under the conditions of a two-fraction gas suspension the burning time of the particles depends weakly on the temperature of the gas. It has also been established that in the region of low gas temperatures, the combustion temperature of the fine fraction is smaller than that of the large fraction. This is explained by the large heat removal from small particles by the molecular-convective process and by the lack of oxidizer in the combustion stage. Oxygen is consumed in the combustion of large particles, which, at low temperatures, ignite earlier. The burning times of particles of coarse and fine fractions of a gas suspension were found. Comparison of the combustion time of small and large particles led to the conclusion that under the conditions of a gas suspension with an excess of an oxidizer close to unity, the particles burn in a diffusion mode. It is shown that the extinction of particles is degenerate. After the moment of extinction, the particles are oxidized in the kinetic regime at a high gas temperature. Проведено фізико-математичне моделювання високотемпературного тепломасообміну та кінетики горіння двофракційного газозавису вуглецевих частинок при різних температурах газу. Передбачалося, що на поверхні вуглецевих частинок протікають дві паралельні хімічні реакції: С+О₂=СО₂ (I), 2С+О₂=2СО (II). Враховувався молекулярно-конвективний теплообмін частинок з газом, а також теплообмін випромінювання зі стінками реакційної установки. В результаті проведеного чисельного експерименту визначені характеристики займання і горіння частинок газозавису в повітрі при різних температурах навколишнього газу. Для розрахунків вибирався двофракційний газозавис з рівними масовими концентраціями фракцій і діаметрами частинок, які відрізняються в 2 рази db₁ = 60 мкм, db₂ = 120 мкм. Діапазон досліджуваних початкових температур газу 1100…1500 К. В результаті проведених розрахунків встановлено, що при зменшенні температури газу частинки великої фракції можуть займатися раніше, ніж частинки дрібної фракції. При високих температурах газу навпаки: період індукції дрібних частинок значно перевищує період індукції частинок великої фракції. Знайдено критичні параметри займання двофракційного газозавису. Основними характеристиками горіння є час і температура горіння частинок. Доведено, що в умовах двофракційного газозавису час горіння частинок мало залежить від температури газу. Також встановлено, що в області низьких температур газу температура горіння частинок дрібної фракції менше, ніж великої. Це пояснюється великим тепловідводом від дрібних частинок молекулярноконвективним шляхом і недостачею окислювача на стадії горіння. Кисень витрачається на горіння великих частинок, які при низьких температурах спалахують раніше. Знайдено часи горіння частинок великої і дрібної фракцій газозавису. Проведено физико-математическое моделирование высокотемпературного тепломассообмена и кинетики горения двухфракционной газовзвеси углеродных частиц при различных температурах газа. Предполагалось, что на поверхности углеродных частиц протекают две параллельные химические реакции: С+О₂=СО₂ (I), 2С+О₂=2СО (II). Учитывался молекулярно-конвективный теплообмен частиц с газом, а также теплообмен излучения со стенками реакционной установки. В результате проведенного численного эксперимента определены характеристики воспламенения и горения частиц газовзвеси в воздухе при различных температурах окружающего газа. Для расчетов выбиралась двухфракционная газовзвесь с равными массовыми концентрациями фракций и диаметрами частиц, которые отличаются в 2 раза: db₁=60 мкм, db₂=120 мкм. Диапазон исследуемых начальных температур газа 1100…1500 К. В результате проведенных расчётов установлено, что при уменьшении температуры газа частицы крупной фракции могут воспламеняться раньше, чем частицы мелкой фракции. При высоких температурах газа наоборот: период индукции мелких частиц значительно превышает период индукции частиц крупной фракции. Найдены критические параметры воспламенения двухфракционных газовзвесей. Основными характеристиками горения являются время и температура горения частиц. Доказано, что в условиях двухфракционной газовзвеси время горения частиц слабо зависит от температуры газа. Также установлено, что в области низких температур газа температура горения частиц мелкой фракции меньше, чем крупной. Это объясняется большим теплоотводом от мелких частиц молекулярно-конвективным путем и недостатком окислителя на стадии горения. Кислород расходуется при горении крупных частиц, которые при низких температурах воспламеняются раньше. Найдены времена горения частиц крупной и мелкой фракций газовзвеси.